Improvement of Ejection Fraction in Patients undergoing Coronary Artery Bypass Grafting with Impaired Left Ventricular Function - Rajbhandari, N.; Sharma Parajuli, S.; Thakur, A.; Dahal, A. (Kathmandu University Medical Journal, 2021)
Background Myocardial revascularization surgery has shown better long term survival expectancy compared to medical therapy in patient with impaired left ventricular function. Objective To evaluate the change in ejection fraction after 90 days in patients who underwent coronary artery bypass surgery and had preoperative left ventricular ejection fraction of less than and equal to 45% in a single cardiac center of Nepal over the period of 2 years. Method Out of 82 eligible patients during 2 years, 3 patients expired in immediate postoperatively and 24 patients had loss of 90 days’ follow up. So, they were excluded from the study. Total 55 patients were taken for the study for whom statistical analysis was done to compare preoperative ejection fraction with post-operative 90 days’ ejection fraction. Result Single vessel disease was present in 2(3.6%) patients, double vessel disease in 7(12.7%) patients and triple vessel disease in 46(83.6%) of the patients. In 2(3.6%) patients 2 grafts, in 18(32.7%) patients 3 grafts, in 33(60%) patients 4 grafts and in 2(3.6%) patients 5 grafts were placed for revascularization. The mean left ventricular EF in preoperative patients was 37.12±5.69% which improved to 45.80±10.00% in postoperative follow up at 90 days which was statistically significant (p=0.000). Conclusion Surgical revascularization of myocardium in preoperatively impaired left ventricular function patients helps improve left ventricular ejection fraction postoperatively. So we suggest surgical revascularization in patient with low ejection fraction for improvement of myocardial function. Hence improve survival rate in these patients.